If We Don't Look, We Won't See: Measuring Language Development to Inform Literacy Instruction. (October 2019) - Adlof, Suzanne M.; Hogan, Tiffany P.
Oral language abilities enable children to learn to read, and they predict future academic achievement and life outcomes. However, children with language impairment frequently go unidentified because schools do not systematically measure oral language development. Given that identification paves the way for treatment, schools should increase attention to oral language development, particularly within response to intervention (RTI) frameworks, which aim to prevent learning disabilities by identifying and intervening at early stages. Formal schooling should address language comprehension (in addition to word reading) to ensure an adequate foundation for future reading comprehension. In support, we overview the developmental relations between oral language abilities and reading skills, review current school-based assessment frameworks, and discuss how these frameworks can include language assessments. Measuring language skills early and often benefits not only those who have language impairment but also all children, as it documents language variability to inform differentiated instruction.